Spin transition nanoparticles made electrochemically. Issue 9 (21st February 2020) - Pozo, Guillermo; de la Presa, Patricia; Prato, Rafael; Morales, Irene; Marin, Pilar; Fransaer, Jan; Dominguez-Benetton, Xochitl
Abstract : Materials displaying novel magnetic ground states signify the most exciting prospects for nanoscopic devices for nanoelectronics and spintronics. Gas-diffusion electrocrystallization is a new method to produce these groundbreaking nanomaterials. Abstract : Materials displaying novel magnetic ground states signify the most exciting prospects for nanoscopic devices for nanoelectronics and spintronics. Spin transition materials, e.g., spin liquids and spin glasses, are at the forefront of this pursuit; but the few synthesis routes available do not produce them at the nanoscale. Thus, it remains an open question if and how their spin transition nature persists at such small dimensions. Here we demonstrate a new route to synthesize nanoparticles of spin transition materials, gas-diffusion electrocrystallization (GDEx), wherein the reactive precipitation of soluble metal ions with the products of the oxygen reduction reaction (ORR), i.e., in situ produced H2 O2, OH −, drives their formation at the electrochemical interface. Using mixtures of Cu 2+ and Zn 2+ as the metal precursors, we form spin transition materials of the herbertsmithite family—heralded as the first experimental material known to exhibit the properties of a quantum spin liquid (QSL). Single-crystal nanoparticles of ∼10–16 nm were produced by GDEx, with variable Cu/Zn stoichiometry at the interlayer sites of Zn x Cu4− x (OH)6 Cl2 . For x = 1 (herbertsmithite) the GDEx nanoparticles demonstrated a quasi-QSL behavior, whereas for x = 0.3 (0.3 < x < 1 for paratacamite) and x = 0 (clinoatacamite) a spin-glass behavior was evidenced. Finally, our discovery not only confirms redox reactions as the driving force to produce spin transition nanoparticles, but also proves a simple way to switch between these magnetic ground states within an electrochemical system, paving the way to further explore its reversibility and overarching implications.